EFFECT OF AQUEOUS AND ETHANOL EXTRACTS OF MELIA AZEDARACH L. AND PENANUM HARMALA L.ON ANTS WORKER APHAENOGASTER MUSCHTIDICA EMERY( HYMENOPTERA : FORMICIDAE) MORTILITY - Al- hadidi , Sanaa Nagem (Diyala Agricultural Sciences Journal, 2013)
The effectiveness of extracts of cold and hot water and ethanol extract of Meliaazedarach L. fruits and seeds Peganumharmala L. tested laboratory against ant workers during a period of 24 hr. Results showed superiority extracts fruits Meliaazedarach L. extracts seeds Peganumharmala L. in achieving higher rates of mortality in value 21.421 , 9.344%, respectively ,as superiority extract ethanol alcohol for both plants on the aqueous extracts cold and hot, amounting ratios mortality of worker ants 17.625 , 15.683 , 12,840% respectively ,also this study appeared that the efficacy insecticidal against worker ants increasing with increase the concentration of the extracts for both plants in value 11.620 , 13.660 ,15.678 ,20.573 %for concentrations 1 ,2.5 ,5 ,10%respectively.